2019
DOI: 10.1007/s41109-019-0127-2
|View full text |Cite
|
Sign up to set email alerts
|

Local bow-tie structure of the web

Abstract: Social networks often has the graph structure of giant strongly connected component (GSCC) and its upstream and downstream portions (IN and OUT), known as a bow-tie structure since a pioneering study on the World Wide Web (WWW). GSCC, on the other hand, has community structure, namely tightly knitted clusters, reflecting how the networks developed in time. By using our visualization of enhanced multidimensional scaling (MDS) and force-directed graph drawing for large and directed graphs, we discovered that a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Innate immune responses are triggered by signaling via pattern-recognition receptors (PRR) such as Toll-like receptors (TLR), double-strand RNA-activated protein kinase R (PKR) and retinoic acid-inducible gene-I (RIG-I)-like receptors that sense pathogen-associated molecular patterns (PAMPs) [6,7]. PRR funnel their signals into interactions with regulated signaling cascades, which then initiate the key antiviral interferon response as well as other common anti-viral and innate immune responses [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Innate immune responses are triggered by signaling via pattern-recognition receptors (PRR) such as Toll-like receptors (TLR), double-strand RNA-activated protein kinase R (PKR) and retinoic acid-inducible gene-I (RIG-I)-like receptors that sense pathogen-associated molecular patterns (PAMPs) [6,7]. PRR funnel their signals into interactions with regulated signaling cascades, which then initiate the key antiviral interferon response as well as other common anti-viral and innate immune responses [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…To perform the tests, we needed information about the firing of neurons, to identify events and cores, and the connections between those neurons, to perform structural analysis of the circuits in which the cores were embedded. Until recently 28 , this double requirement was impossible to fulfill. The MICrONS project 21 now gives this opportunity by releasing electron microscopy (EM) and co-registered two-photon calcium imaging datasets of the same cortical tissue (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given that our data and models are directed, and that our focus is on the flow of information, we identified modules as the most frequented subgraphs spanned by (hundreds of) random walks over directed edges 52 . Once modules were identified, the convergent-divergent bow-tie organization 27,28 of each module was assessed by finding its largest subgraph component (Fig. 3C, inset green), then verifying the existence of an in-component – projecting to the largest (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By modeling the websites and pages on the Web, Broder et al [12] discovered that it has a bow-tie structure, with most accessible pages in a giant strongly connected component (GSCC) and pages that have not been linked yet to the GSCC in the IN or OUT component (the sides of the bow tie). A recent study [13] has shown the presence, on the Web, of local bow-tie structures, as most websites tend to focus on specific topics and content, being able to rely on traffic from loyal online users and frequent visitors.…”
Section: Introductionmentioning
confidence: 99%